Longitudinal analysis of symptoms in the Ehlers‐Danlos syndromes. Issue 4 (7th January 2022) - Schubart, Jane R.; Mills, Susan E.; Schaefer, Eric W.; Bascom, Rebecca; Francomano, Clair A.
Abstract: Our study extends a cross‐sectional dataset on the Ehlers‐Danlos syndromes (EDS) assembled by the National Institute on Aging (NIA), under a protocol entitled Clinical and Molecular Manifestations of Heritable Disorders of Connective Tissue . We were successful in contacting 171 of the original 252 participants with EDS. Our study cohort included 91 participants who completed at least one of the following surveys: Brief Pain Inventory (BPI), Pittsburgh Sleep Quality Index (PSQI), Multidimensional Fatigue Inventory (MFI‐20), and Short Form (SF‐36) Health Survey, at both baseline and follow‐up. Follow‐up surveys occurred a median of 11.6 years after the baseline survey. We used mixed effects linear regression models to examine the change in scores for multiple indices reported by participants. There were small mean changes reflected in our estimates for the EDS population as a whole. There was wide heterogeneity between reported individual experiences, with some participants markedly improved and some dramatically worse. Men had a greater increase in mean pain severity over time than women. This is the first study to report a decade of longitudinal data in EDS.